Management of Educational Development Contribution Program in Improving Student Learning Achievement in Islamic Boarding Schools At-Taufiq Petapahan - Aflizah, Nur; Hartono, Hartono; Mudasir, Mudasir (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
Islamic boarding schools as traditional Islamic educational institutions play an important role in shaping the character and intelligence of students, but it is not uncommon to face obstacles in the aspect of funding, especially related to limited government support and conventional management of internal resources. One of the strategies implemented by the At-Taufiq Petapahan Islamic Boarding School to overcome these limitations is through the management of the Education Development Contribution Program (SPP) which is used not only for institutional operations, but also as a tool to improve the quality of student education. This study aims to analyze how the management of the SPP program is carried out in improving student learning achievement, focusing on aspects of planning, implementation, and program evaluation. Using a descriptive qualitative approach, data was collected through in-depth interviews, direct observations, and administrative documentation involving pesantren leaders, treasurers, school committees, and madrasah heads. The results of the study show that the management of the SPP program is carried out in a structured and participatory manner, with a transparent and accountable reporting system. This program is able to provide better educational facilities, provide scholarships to underprivileged outstanding students, and support the development of curriculum and character-based learning activities. The conclusion of this study is that effective and sustainable management of tuition programs can improve students' learning achievement in both cognitive, affective, and psychomotor aspects, as well as encouraging the independence of Islamic boarding schools in managing their finances without full dependence on external funds. This research makes a real contribution to the discourse on Islamic education financial management and can be used as a reference for similar educational institutions in implementing a financing management model based on community participation.